Diagnostic accuracy of tests to detect Hepatitis C antibody: a meta-analysis and review of the literature - Tang, Weiming; Chen, Wen; Amini, Ali; Boeras, Debi; Falconer, Jane; Kelly, Helen; Peeling, Rosanna; Varsaneux, Olivia; Tucker, Joseph D.; Easterbrook, Philippa (BMC infectious diseases, 2017)
Although direct-acting antivirals can achieve sustained virological response rates greater than 90% in Hepatitis C Virus (HCV) infected persons, at present the majority of HCV-infected individuals remain undiagnosed and therefore untreated. While there are a wide range of HCV serological tests available, there is a lack of formal assessment of their diagnostic performance. We undertook a systematic review and meta-analysis to evaluate he diagnostic accuracy of available rapid diagnostic tests (RDT) and laboratory based EIA assays in detecting antibodies to HCV. We used the PRISMA checklist and Cochrane guidance to develop our search protocol. The search strategy was registered in PROSPERO (CRD42015023567). The search focused on hepatitis C, diagnostic tests, and diagnostic accuracy within eight databases (MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, Science Citation Index Expanded, Conference Proceedings Citation Index-Science, SCOPUS, Literatura Latino-Americana e do Caribe em Ciências da Saúde and WHO Global Index Medicus. Studies were included if they evaluated an assay to determine the sensitivity and specificity of HCV antibody (HCV Ab) in humans. Two reviewers independently extracted data and performed a quality assessment of the studies using the QUADAS tool. We pooled test estimates using the DerSimonian-Laird method, by using the software R and RevMan. 5.3. A total of 52 studies were identified that included 52,673 unique test measurements. Based on five studies, the pooled sensitivity and specificity of HCV Ab rapid diagnostic tests (RDTs) were 98% (95% CI 98-100%) and 100% (95% CI 100-100%) compared to an enzyme immunoassay (EIA) reference standard. High HCV Ab RDTs sensitivity and specificity were observed across screening populations (general population, high risk populations, and hospital patients) using different reference standards (EIA, nucleic acid testing, immunoblot). There were insufficient studies to undertake subanalyses based on HIV co-infection. Oral HCV Ab RDTs also had excellent sensitivity and specificity compared to blood reference tests, respectively at 94% (95% CI 93-96%) and 100% (95% CI 100-100%). Among studies that assessed individual oral RDTs, the eight studies revealed that OraQuick ADVANCE® had a slightly higher sensitivity (98%, 95% CI 97-98%) compared to the other oral brands (pooled sensitivity: 88%, 95% CI 84-92%). RDTs, including oral tests, have excellent sensitivity and specificity compared to laboratory-based methods for HCV antibody detection across a wide range of settings. Oral HCV Ab RDTs had good sensitivity and specificity compared to blood reference standards.